(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
Food safety and waste reduction are critical challenges in modern supply chain systems. This paper presents an AI-enabled Food Batch Tracking and Expiry Alert Management System designed to monitor food batches in real time and provide intelligent expiry alerts. The system integrates IoT sensors, barcode/QR-based tracking, and machine learning algorithms to predict shelf life and detect potential spoilage risks. A centralized backend manages batch-level data, while AI models analyze environmental conditions such as temperature and humidity. Experimental results show improved accuracy in expiry prediction and reduction in food wastage. The system is scalable, cost-effective, and suitable for industries such as retail, logistics, and food processing